A fully coupled material constitutive model for steel quench analysis. (20th January 2011) - Yao, Xin; Zhu, Lihua; Li, M. Victor
The residual stresses and distortion induced by quenching in an eccentric ring were investigated in this study with finite element method. The ring was made of AISI 52100 steel. A fully coupled 3D temperature-displacement analysis was performed to simulate heat transfer, phase transformations and mechanical stresses and strains during the heating and subsequent quenching processes. Commercial FEA package ABAQUS/Standard 6.4 was used for the analyses along with user subroutines developed by the authors to model the thermal and mechanical constitutive behaviour. The eccentric ring was subjected to three stress analysis in response to temperature, martensitic transformation and transformation plasticity, respectively. Simulation results indicated that thermal stress leaves the surface in compressive and the core in tensile. Martensitic transformation dilation in the surface pushes the compressive stress to a higher level in the early stage of quenching, but the subsequent dilation in the core nearly counteracts the tensile stress there. The quenching residual stresses change the signs with the addition of transformation plasticity, which also induces significant plastic strains during quenching. Quenching distortion experiments are in accordance with the simulation results which take transformation plasticity into consideration.